2021
DOI: 10.36660/abc.20190437
|View full text |Cite
|
Sign up to set email alerts
|

Os Efeitos da Doxorrubicina na Biossíntese e no Metabolismo do Heme em Cardiomiócitos

Abstract: Resumo Fundamento A doxorrubicina está associada à cardiotoxicidade e à morbidade cardíaca tardia. O heme está relacionado ao stress oxidativo celular. Entretanto, sua regulação específica em cardiomiócitos sob os efeitos de doxorrubicina ainda não foi documentada. Objetivo Nosso objetivo é avaliar as alterações de enzimas limitantes de velocidade no caminho metabólico do heme sob o efeito de doxorrubicina. Métodos Cardiomiócitos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…These two datasets were based on a doxorubicin-induced acute heart injury mouse model performed through intraperitoneal administration of doxorubicin in a dose of 15 mg/kg for 4 or 5 days [ 25 , 26 ]. After combining and reanalyzing the datasets, we screened out a total of 120 DEGs between the normal myocardial tissue and the toxic myocardial tissue, of which parts were confirmed by previous reports in terms of the expression trend, such as Ctgf [ 27 ], Aox1 [ 28 ], Alas2 [ 29 ], and Ly86 [ 30 ]. However, Btg2 was upregulated after doxorubicin treatment in our study, while a previous study found it to be downregulated [ 31 ].…”
Section: Discussionmentioning
confidence: 73%
“…These two datasets were based on a doxorubicin-induced acute heart injury mouse model performed through intraperitoneal administration of doxorubicin in a dose of 15 mg/kg for 4 or 5 days [ 25 , 26 ]. After combining and reanalyzing the datasets, we screened out a total of 120 DEGs between the normal myocardial tissue and the toxic myocardial tissue, of which parts were confirmed by previous reports in terms of the expression trend, such as Ctgf [ 27 ], Aox1 [ 28 ], Alas2 [ 29 ], and Ly86 [ 30 ]. However, Btg2 was upregulated after doxorubicin treatment in our study, while a previous study found it to be downregulated [ 31 ].…”
Section: Discussionmentioning
confidence: 73%
“…A high number of mitochondria and low antioxidant defense of cardiomyocytes make these cells vulnerable to oxidative damage by ROS [ 62 , 63 , 64 , 65 ]. Dox-induced production of ROS leads to dysregulated calcium and iron transport [ 61 , 64 , 65 ] and reduced oxidative phosphorylation (respiration) and ATP production [ 64 , 65 , 66 ]. Dox was also shown to block the antioxidant system in cardiac muscles, represented by the sirtuins family proteins SIRT1 and SIRT3 [ 67 , 68 ].…”
Section: Genetic Polymorphisms and Cardiotoxicity In Dox-treated Pati...mentioning
confidence: 99%